Trade policy in Asia higher education and media services - Findlay, Christopher (World Scientific Pub. Co., 2014)
Education and media services have much in common. Both provide services that embody local cultures, in which there is extensive public sector participation and significant domestic regulation. At the same time, both are dramatically affected by the information and communications technology revolution. The production of information content now involves huge costs in terms of research and development or artistic talent, whilst the cost of making such products available to other consumers is very low. This in turn challenges the effectiveness of domestic regulation and raises fundamental questions about its purpose, calling for an increased scope for international trade and investment, and the development of supply chains. Yet, both areas are lightly committed in international trade agreements like the GATS. This lack of commitment and the lack of additional impact from negotiations in bilateral discriminatory trade agreements are cross-cutting themes in the book.
Keywords: Education, Higher / Economic aspects / Asia; Transnational education / Economic aspects / Asia; Mass media / Economic aspects / Asia